mHealth Physical Activity Intervention: A Randomized Pilot Study in Physically Inactive Pregnant Women - Choi, JiWon; Lee, Ji hyeon; Vittinghoff, Eric; Fukuoka, Yoshimi (Maternal and child health journal, 2016)
Introduction Physical inactivity is prevalent in pregnant women, and innovative strategies to promote physical activity are strongly needed. The purpose of the study was to test a 12-week mobile health (mHealth) physical activity intervention for feasibility and potential efficacy. Methods Participants were recruited between December 2012 and February 2014 using diverse recruitment methods. Thirty pregnant women between 10 and 20 weeks of gestation were randomized to an intervention (mobile phone app plus Fitbit) or a control (Fitbit) group. Both conditions targeted gradual increases in physical activity. The mHealth intervention included daily messages and a mobile phone activity diary with automated feedback and self-monitoring systems. Results On monthly average, 4 women were screened for initial eligibility by telephone and 2.5 were randomized. Intervention participants had a 1096 ± 1898 step increase in daily steps compared to an increase of 259 ± 1604 steps in control participants at 12 weeks. The change between groups in weekly mean steps per day during the 12-week study period was not statistically significant ( p = 0.38). The intervention group reported lower perceived barrier to being active, lack of energy, than the control group at 12-week visit ( p = 0.02). The rates of responding to daily messages and using the daily diary through the mobile app declined during the 12 week study period. Discussion It was difficult to recruit and randomize inactive women who wanted to increase physical activity during pregnancy. Pregnant women who were motivated to increase physical activity might find using mobile technologies in assessing and promoting PA acceptable. Possible reasons for the non-significant treatment effect of the mHealth intervention on physical activity are discussed. Public awareness of safety and benefits of physical activity during pregnancy should be promoted. Clinicaltrials.Gov Identifier NCT01461707.